PENGARUH JUMLAH BARIS TANAMAN PERANGKAP PADA TANAMAN CABAI MERAH (Capsicum annum L.) UNTUK MENGENDALIKAN SERANGAN KUTU DAUN Aphis gossypii Glover (HOMOPTERA: APHIDIDAE) - Salbiah, Desita; Sutikno, Agus; Turnip, Boby Pamrianus (PEST Tropical Journal, 2013)
Aphis gossypii (Homoptera: Aphididae) is major pest in red pepper plant who may createdamage. This study aims to test amount row trap plant in order to control attack leaf bug Aphisgossypii Glover (Homoptera: Aphididae) at red pepper plants (Capsicum annum L.). Thisresearch was conducted at the Technical Organizer Unit Trial Garden and Laboratory Plant PestFaculty Agricultural University of Riau, from June to August 2013. This research was carriedout by using a randomized block design (RBD) with 5 treatments and 4 replication withoutplanting trap plant, 2 rows red pepper 1 row mustard, 1 row red pepper 2 rows mustard, 1 rowred pepper 3 rows mustard, 2 rows red pepper 2 rows mustard. The results of the study showedthat planting 2 rows red pepper 2 rows mustard is better because leaf bug trapped too much fromtreatment else with average 22,87 tails in red pepper and 23,06 tails in mustard. Every reductionof populations one tail leaf bug in red pepper, then populations of leaf bug in mustard to go up0,763 %.Keyword: Red pepper (Capsicum annum L.), Aphis gossypii Glover, and mustard (Brassicajuncea L.)